A case study on agreement between self-reported bicycle accidents and hospital and police records - Møller, Katrine Meltofte; Madsen, Tanja K. O.; Olesen, Anne Vingaard; Lahrmann, Harry (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
A self-report questionnaire on bicycle accidents was distributed to 6,793 respondents every month for one year (2012/2013). This paper evaluates the agreement between hospital data, police data, and self-reports concerning the number of accidents, as well as the information recorded regarding each accident. Six hundred and ninety-four accidents were self-reported by 6,793 respondents. In 99 cases, the respondents reported getting medical care at a hospital. Of these self-reported contacts, 74 could be matched to a hospital record, but only 53 of the 74 were registered in the hospital records as traffic accidents. Information on the primary opposite party in the 53 accidents was compared, and moderate agreement was found between self-reports and hospital records (κ=0.63). In 23 of the self-reported accidents, it was stated that a police report had been recorded, but only 6 accidents could be located in the police records. The sample size was too small to calculate statistical agreement between police records and self-reports. These findings are relevant to discuss of the level of underreporting of bicycle accidents in Denmark because they indicate that there could be substantially more accidents than noted in official records. Furthermore, this paper provides insight into methodological issues associated with self-reporting of traffic accidents.